In Cilico Study and Genetic Variation of Genus Rhododendron using DNA Barcode trnL–trnF Intergenic Spacer - Chika, Syifara (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2024)
Rhododendron is a flowering plant which is the largest genus in the Ericaceae family. Around 1,157 Rhododendron species have been assessed using the IUCN Red List criteria, and 316 are categorized as endangered species. Apart from maintaining species population numbers, conservation activities also need to pay attention to genetic aspects through DNA barcoding techniques. This research uses molecular in-silico methods using sequence data from NCBI's GenBank. This research aims to carry out an inventory of Rhododendron types based on genetic aspects, analyzing genetic variations and kinship relationships in the Rhododendron Genus. The resulting phylogenetic tree is divided into three clades in the Rhododendron group and one outgroup. The phylogenetic tree results show that the trnL-trnF DNA barcode can differentiate and identify up to species level in the genus Rhododendron. The trnL-trnF DNA barcode region of the Rhododendron genus is mostly conserved because it only has eight genetic variations, namely T71C, G225C, T245C, T229A, T485C, A491G, T705C, and A783G. The trnL-F gene is an informative chloroplast and can show the relationship between types.